1996
DOI: 10.1159/000217993
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Thymidylate Synthase Gene Expression Levels by Semi-Quantitative Competitive Reverse Transcriptase Polymerase Chain Reaction followed by Quantitative Digital Image Analysis

Abstract: We describe a simplified and reliable polymerase chain reaction (PCR) method to quantify thymidylate synthase (TS) gene expression levels from clinical human tumor biopsy samples as small as 100 mg using the Β-actin housekeeping gene as a reference standard. The semiquantitative RT-PCR is carried out by the coamplification of the target template and an external competitor using primer pairs common to both templates in the same reaction vessel. Quantitative digital image analysis is performed directly after ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…By using several dilutions of the reference gene, the absolute concentration of target cDNA is established when the amplification of both genes are equal. However, it is extremely difficult to find synthetic genes that are amplified with the same efficiency as the target gene, and the efficiencies decrease in a nonequivalent manner at different starting concentrations of the genes [6,7]. This method also requires gel electrophoretic resolution and densitometric analysis of two closely migrating DNA fragments after completion of the PCR, which implies considerable manual dexterity and makes it less suitable for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…By using several dilutions of the reference gene, the absolute concentration of target cDNA is established when the amplification of both genes are equal. However, it is extremely difficult to find synthetic genes that are amplified with the same efficiency as the target gene, and the efficiencies decrease in a nonequivalent manner at different starting concentrations of the genes [6,7]. This method also requires gel electrophoretic resolution and densitometric analysis of two closely migrating DNA fragments after completion of the PCR, which implies considerable manual dexterity and makes it less suitable for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital image analysis (DIA) following silver nitrate staining of polyacrylamide gels to di rectly quantify the PCR products eliminates the need for the use of radioactive substances in quantitative RT-PCR. Quantitative DIA (Q-DIA) enables the rapid and direct quanti fication of the concentrations of amplifica tion products [15,21,22], Furthermore, Q-DIA has recently been used to compare the observed level of TS gene expression relative to intracellular enzyme activity levels in shock-frozen clinical biopsy specimens of normal and tumor tissues [23], In the present study, this new method of Q-DIA analysis will be coupled with a novel method of mRNA extraction from formalin-fixed paraf fin-embedded samples, to analyze TS gene expression levels for normal and tumor biop sies from the same patients with the hope of gaining retrospectively insight into mecha nisms of tumor progression and resistance to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RT-PCR provides a means by which the sensitivity of PCR in the detection of specific genes can provide many advantages over previous methods, especially in gene expression studies (2,4,(7)(8)(9)(10)(11). By modifying the method of mRNA extraction outlined by de Andrés et al (3) by the addition of sonification, it has been shown that archival biopsy sections can be used as a source of intact mRNA for retrospective gene expression studies.…”
Section: Introductionmentioning
confidence: 99%